Historia nie jedyna - Konieczna, Maria (Warszawa : Volumen, 1990)
Memoirs of a Jewish lady about life in Lwow, Poland before WW II and afterwards.
Keywords: Konieczna, Maria; World War, 1939-1945 -- Personal narratives, Jewish; Jews -- Poland -- Biography